A Versatile Protocol for the Synthesis of Pyrazolyl‐Substituted Pyridinium and Guanidinium Salts from Pyridone and Urea Derivatives. Issue 34 (27th October 2014) - Echterhoff, Antje K. C.; Yogendra, Sivathmeehan; Kösters, Jutta; Fischer, Roland; Weigand, Jan J.
Abstract: The trication (pyr3 P2 ) 3+ (1 +, pyr = 3, 5‐dimethylpyrazolyl) is used as a convenient pyrazolyl‐transfer reagent to convert 2‐pyridones, 4‐pyridones, and urea derivatives to pyrazolyl‐substituted pyridinium or guanidinium triflate salts. This conversion represents a new, efficient, and highly functional‐group‐compatible approach that yields the desired products conveniently and in high yields. Typically, this reaction proceeds by exchange of the carbonyl oxygen atom of the substrate for a pyrazolyl moiety. However, for the structurally related 3‐hydroxypyridines, a different reaction pathway occurs to give tripyridyl phosphites. The outcome of the reaction can be explained by the lactam–lactim tautomerism of the substrate and is discussed in detail. All reaction products were fully characterized by elemental analysis and multinuclear NMR, IR, and Raman spectroscopy, and the structural arrangements of most of the products were confirmed by X‐ray crystallography analysis. Abstract : The Janus head type diphosphorus trication (pyr3 P2 ) 3+ (pyr = 3, 5‐dimethylpyrazolyl) is used as pyrazolyl‐transfer reagent to convert 2‐pyridones, 4‐pyridones, and urea derivatives to pyrazolyl‐substituted pyridinium or guanidinium triflate salts. The lactam–lactim tautomerism controls the reaction outcome. Thus, under lactim‐favoring conditions, tripyridyl phosphites are formed in these reactions.